Trichoderma asperellum Inoculation as a Tool for Attenuating Drought Stress in Sugarcane - Scudeletti, Daniele [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Bossolani, Joao William [UNESP]; Moretti, Luiz Gustavo [UNESP]; Momesso, Letusa [UNESP]; Servaz Tubana, Brenda; Castro, Sergio Gustavo Quassi de; De Oliveira, Elisa Fidencio [UNESP]; Hungria, Mariangela (Frontiers Media Sa, 2021)
Drought stress is an important concern worldwide which reduces crop yield and quality. To alleviate this problem, Trichoderma asperellum has been used as a plant growth-promoting fungus capable of inducing plant tolerance to biotic and abiotic stresses. Here, we examined the effect of T. asperellum inoculation on sugarcane plant above and belowground development under drought stress and investigated the role of this fungus on inducing tolerance to drought at physiological and biochemical levels. The experiment was performed in pots under greenhouse conditions, with four treatments and four replicates. The treatments consisted of sugarcane plants inoculated or not with T. asperellum and grown under drought stress and adequate water availability. Drought-stressed sugarcane plants inoculated with T. asperellum changed the crop nutrition and chlorophyll and carotenoid concentrations, resulting in increased photosynthesis rate, stomatal conductance, and water use efficiency compared to the non-inoculated plants. In addition, the antioxidant metabolism also changed, increasing the superoxide dismutase and peroxidase enzyme activities, as well as the proline concentration and sugar portioning. These cascade effects enhanced the root and stalk development, demonstrating that T. asperellum inoculation is an important tool in alleviating the negative effects of drought stress in sugarcane. Future studies should be performed to elucidate if T. asperellum should be reapplied to the sugarcane ratoons.
Keywords: Plant growth promoting fungus; low water availability; reactive oxygen species; antioxidant metabolism; Saccharum officinarum L